Comparison of urinary parameters, biomarkers, and outcome of childhood systemic lupus erythematosus early onset-lupus nephritis - Miguel, Daniele Faria [UNESP] (2020)
Background: Urinary parameters, anti-dsDNA antibodies and complement tests were explored in patients with childhood-Systemic Lupus Erythematosus (cSLE) early-onset lupus nephritis (ELN) from a large multicenter cohort study. Methods: Clinical and laboratory features of cSLE cases with kidney involvement at presentation, were reviewed. Disease activity parameters including SLEDAI-2 K scores and major organ involvement at onset and follow up, with accrued damage scored by SLICC-DI, during last follow up, were compared with those without kidney involvement. Autoantibodies, renal function and complement tests were determined by standard methods. Subjects were grouped by presence or absence of ELN. Results: Out of the 846 subjects enrolled, mean age 11.6 (SD 3.6) years; 427 (50.5%) had ELN. There was no significant difference in the ELN proportion, according to onset age, but ELN frequency was significantly higher in non-Caucasians (p = 0.03). Hematuria, pyuria, urine casts, 24-h proteinuria and arterial hypertension at baseline, all had significant association with ELN outcome (p < 0.001). With a similar follow up time, there were significantly higher SLICC-DI damage scores during last follow up visit (p = 0.004) and also higher death rates (p < 0.0001) in those with ELN. Low C3 (chi-square test, p = 0.01), but not C3 levels associated significantly with ELN. High anti-dsDNA antibody levels were associated with ELN (p < 0.0001), but anti-Sm, anti-RNP, anti-Ro, anti-La antibodies were not associated. Low C4, C4 levels, low CH50 and CH50 values had no significant association. High erythrocyte sedimentation rate (ESR) was associated with the absence of ELN (p = 0.02). Conclusion: The frequency of ELN was 50%, resulting in higher morbidity and mortality compared to those without ELN. The urinary parameters, positive anti-dsDNA and low C3 are reliable for discriminating ELN.